ERROR ANALYSIS OF NON–ENGLISH STUDENTS IN WRITING NARRATIVE TEXT - Yaqin, Ainul (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2024)
This study aims to analyze the common errors that students made in writing Narrative Text. This study was made in November of their first semester. In getting data, the writer used descriptive analysis and purposive sampling to determine the subject of samtple. This study is undertaken at Islamic Education Major of Sekolah Tinggi Agama Islam (STAI) Islamic Centre Demak in the first semester of the academic years of 2023/2024. The participants of the study were three students of Islamic Education Major of STAI IC Demak. The findings indicate that Word Form (13,25%), Word Choice (6,20%), Verb Tense (32,55%), Add/ Omit Word (12,04%), Spelling (7,22), Punctuation (7,22%), Capitalization (13,25%), Article (6,63%), Singular-Plural (3,61%), Word Order (1,20%), Incomplete Sentence (2,40%), Meaning Not Clear (6,02%), Run-on Sentence (5,61%). So, this study states that the most students’ error types are verb tense because of Intralingual Transfer and Overgeneralization.